A meta-analysis of the meaning in life and suicidal ideation based on Chinese samples - Yang, Xinguo; Xiao, Lei; Lan, Yuanmei; Xue, Jingdan; He, Yunxiao (Frontiers in Psychology, 2025)
Previous research has examined the link between meaning in life and suicidal ideation across cultures, highlighting cultural background as a moderator. However, few studies focus on single cultural contexts. To address this gap within China, this meta-analysis investigates the association between meaning in life and suicidal ideation, specifically examining moderators including regional economic differences, measurement tools for suicidal ideation, and the impact of public health emergency (e.g., COVID-19). Results show a negative correlation between meaning in life and suicidal ideation [r = −0.387, 95% CI (−0.425, −0.344)]. Subgroup analyses revealed stronger effects in undeveloped regions, when using specific measurement tools, and during public health emergency. Unlike previous studies, gender did not significantly moderate this relationship. These findings confirm that enhancing meaning in life may be a key protective factor against suicidal ideation in China, especially in undeveloped regions and during crises. Future interventions should develop tailored strategies to strengthen meaning in life, prioritizing economic inequality and crisis resilience.